(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2010)
The main function of the auditing process is to get a financial report provide information about the activities of the economic entities. The financial report’s information is intended to be useful in making decisions and planning for entities future. Such information became more effective and efficient if the auditors process analytical auditing procedures, by using those financial analysis tools, which mean more detailed indicators. The objectives of this research are to investigate auditor’s use of analytical procedures in Oman and identify the main objectives for using these procedures. A questionnaire was used to gather the data for the study. A sample of 65 auditors and the response rate was 80% (52). The results of the study indicated that majority of auditors conducted the importance of the use of analytical procedures and other analytical tools to get useful information from that accounting data.